2017
DOI: 10.1111/cts.12483
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous Hydroxypropyl β‐Cyclodextrin Formulation of Letermovir: A Phase I, Randomized, Single‐Ascending, and Multiple‐Dose Trial

Abstract: Letermovir is a novel antiviral in clinical development for prophylaxis against human cytomegalovirus in immunocompromised transplant recipients. This two-part, single-center, randomized, double-blind, placebo-controlled trial evaluated the safety and pharmacokinetics of a hydroxypropyl β-cyclodextrin (HPβCD)-based intravenous formulation of letermovir in healthy women. Subjects received single, escalating doses (120, 240, 480, 720, and 960 mg; 6 letermovir, 2 placebo per cohort) or multiple, oncedaily doses (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 12 publications
1
21
0
Order By: Relevance
“…175,176 Additionally, HP-β-CD is known to reduce local irritation antiviral intravenous formulation of letermovir. 177 These studies unlock new avenues in the research of drug delivery science for better management opportunities of diseases and their side effects.…”
Section: Conclusion and Future Perspectivementioning
confidence: 99%
“…175,176 Additionally, HP-β-CD is known to reduce local irritation antiviral intravenous formulation of letermovir. 177 These studies unlock new avenues in the research of drug delivery science for better management opportunities of diseases and their side effects.…”
Section: Conclusion and Future Perspectivementioning
confidence: 99%
“…A limitation of this study was that only single doses of fluconazole and letermovir were administered when it would be likely that these drugs would be coadministered in multiple doses. However, the PK of fluconazole 13‐15 and letermovir 16 after multiple‐dose administration was consistent with single‐dose administration, including the lack of expected accumulation. This suggests that the effects observed in this study following single doses are not expected to be different from those observed after multiple doses.…”
Section: Discussionmentioning
confidence: 62%
“…For instance, HP-β-CD has been proved to be an effective excipient in the intravenous administration of Letermovir, an antiviral developed to deal with cytomegalovirus (CMV) in immunocompromised patients, such as transplant recipients or seropositive individuals (Fig. 3) (Erb-Zohar et al, 2017). The effectiveness of this formulation in phase III essays, without significant adverse events (Marty et al, 2017), lead to the approval of the treatment, now available as Prevymis TM Injection.…”
Section: Modified Cyclodextrins In General Antiviral Formulationsmentioning
confidence: 99%